At work for sustainability - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A workshop on exchanging experiences about the use of participatory approaches and sustainable agriculture will be organised by the Sustainable Agriculture Centre for Research, Extension and Development in Africa (SACRED Africa), from 13 to 18...